The Correlation between Knowledge Level and Personal Hygiene with Scabies Occurrence in Miftahul Ulum Islamic Boarding Schools Jember Regency - Anthia Ayu Nandira; Yunita Armiyanti; Rini Riyanti (Journal of Agromedicine and Medical Sciences, 2021)
Scabies is caused by infestation and sensitization of Sarcoptes scabiei hominis varieties. Scabies is easily transmitted to individuals who live in groups such as boarding schools. Knowledge of scabies that is lacking and low in individual hygiene among student causes a transmission to be faster and wider. The purpose of this study was to determine the relationship between the characteristics, level of knowledge and individual hygiene of the student with the occurrence of scabies at the Miftahul Ulum Islamic Boarding School in Kalisat District, Jember Regency. This study used an observational analytical method with cross-sectional. Of the population of 358 students, 229 students were willing to become respondents. The results showed that 105 students (45.9%) suffered from scabies. The chi-square test results showed the characteristics of respondents such as gender, pruritus complaints, pruritus onset when entering the hut, treatment history was associated with the incidence of scabies (p <0.05). Risk factors for individual hygiene in the form of using towels alternately and washing towels together were also associated with the incidence of scabies (p <0.05). Bivariate analysis at the level of individual knowledge and hygiene as a whole showed no significant association with the incidence of scabies (p> 0.05). The result of multiple logistic regression test showed 2 variables, namely, sex and pruritus onset when entering the lodge significantly associated with the incidence of scabies (p <0.05). Keywords : scabies, knowledge level, personal hygiene